Emergent Interfacial Ferromagnetism and Exchange Bias Effect in Paramagnetic/Ferromagnetic Oxide Heterostructures. Issue 21 (13th September 2020) - Bhatt, Harsh; Kumar, Yogesh; Prajapat, Champa Lal; Kinane, Christy J.; Caruana, Andrew; Langridge, Sean; Basu, Saibal; Singh, Surendra
Abstract: The experimental evidence of the exchange bias (EB) effect in epitaxial heterostructures of ferromagnetic La0.67 Sr0.33 MnO3 (LSMO) and paramagnetic LaNiO3 (LNO) grown on MgO(001) substrates is reported. The macroscopic magnetization measurements show a clear indication of EB in LNO/LSMO and LSMO/LNO/LSMO heterostructures. The strength of the exchange coupling rapidly reduces as the temperature is increased and almost vanishes above 50 K. Using spin dependent polarized neutron reflectometry (PNR) detailed depth dependent magnetization profiles of the heterostructures are investigated to understand the role of interface magnetism in the observed EB. PNR results establish the emergence of the interfacial ferromagnetic LNO layer of thickness ≈22–35 Å (≈6–9 unit cell) and magnetization ≈80 emu cc −1 at the LNO/LSMO interface for T  < 100 K. The PNR results also show both ferromagnetic and anti‐ferromagnetic coupling between the LSMO and interfacial LNO layers, which may be dependent on the stacking order. The emergence of ferromagnetism in the interfacial paramagnetic LNO layer with unexpected EB in these heterostructures suggests a promising platform toward the effective realization of magnetic devices. Abstract : Polarized neutron reflectometry (PNR) results establish the emergence of the interfacial ferromagnetic LNO layer of thickness ≈6–9 unit cell and magnetization ≈80 emu cc −1 at the LNO/LSMO interface for T  < 100 K. The PNR results also show both ferromagnetic and anti‐ferromagnetic coupling between the LSMO and interfacial LNO layers, which depends on the stacking order.